Grundtvig og Spener. Især til belysning af den pietistiske Grundtvig - Thyssen, A. Pontoppidan (Grundtvig-Studier, 1967)
Grundtvig and Spener With Grundtvig the Pietist as Chief Object of Illustration By A. Pontoppidan Thyssen The question of pietistic elements in Grundtvig’s theology has received much attention in both religious and scholarly debate. By way of illustration the present treatise attempts a comparative analysis of leading ideas in Grundtvig and Ph. J. Spener, the central figure of German pietism. The author first deals with Spener’s views as expressed in the programmatic treatise Pia Desideria (1675). The leading ideas are epitomised under four viewpoints: 1. The starting-point is a general criticism of religious conditions in all classes of society. Very few understand and practise Christianity in the right way; the clergy itself has been spoilt by the world spirit, and most laymen are Christian in name only.—2. The criticism is placed in a historical perspective: the time following the Reformation has been a disappointment like the history of Israel after the return from Babylon; the Lutheran Church has been devoid of life like the Church in Sardis mentioned in the Apocalypse. But now the reformation is to be completed and the ideal condition of the first Church is to be approached.— 3. Spener’s confidence in God’s power and promises is the basis of his optimism; in addition a strong appeal is made in support of working for the cause of the Church, which is also, however, conceived theocentrically as the working of the power of the Word to the inner rebirth of man and the gradual growth of goodness.—4. The consequence of this attitude is a sharp distinction between the reborn and »the world«, and the Church cannot just be identified with the State church the spiritual coercion of which is denounced by Spener; it is really the invisible community of the truly faithful in all religious communities. All these chief points of view will be found in Grundtvig also, but significant modifications are clearly brought out by the comparison: 1. Grundtvig’s starting-point is also a strong criticism of religious conditions, especially after his religious crisis of 1810 -11, which had affinities with the pietistic conversion. Like Spener he directed his criticism against the immorality and religious indifference of the age, but besides he attacked the false doctrine of the clergy. When in the 1820’s he had found in the sacraments the foundation of true Christianity, polemics receded into the background, but his Christian evaluation of his age and of religious life in general was not moderated. 2. In Grundtvig, too, religious criticism was connected with a historical perspective corresponding closely to what we find in Spener. The ideal was to be found in the oldest Church; after the decline of the Middle Ages the Reformation brought a renewal, but the renewal was not completed; like the dying Church in Sardis the Lutheran Church was subject to »scripturalism« and State-church compulsion, and the pietistic »rebellion« did not succeed in creating new life. It is only with Grundtvig’s own achievement that a new era for the Church is heralded after “ the fountain of life” in baptism has been found. As regards confidence in the present and the future Grundtvig surpasses Spener; the growing optimism can be followed in his sermons where the renewal of congregational life through the Grundtvigian movement is increasingly emphasized; the popular revival is pointed to in this connection as the working, through the renewed Church, of the Spirit of God. 3. The basis of this optimism is also in Grundtvig a markedly theocentric outlook: both the renewal of the Church and the growth of Christian life in the individual depend on “ the divine force of life” which in Grundtvig’s opinion is to be found only in the Word of God as spoken at baptism and Holy Communion. The ethical appeal typical of Spener is not found in Grundtvig, but he, too, set great store by the growth of Christian life and the “ recognizability” of the Church and the Christian community. On the other hand the renewal is not linked up closely with the rebirth of “ the inner man” , it is a redemption of the whole of natural human life; and just as the Word of the sacrament is the only source of strength, Christian life really finds its sole unambigious expression in the words of confession, preaching, and hymns of praise. 4. Owing to Grundtvig’s idea of the “ recognizability” of the Christian community we find him stressing, as strongly as did Spener, the distinction between the Christians and “ the world” . Especially in his sermons “ the world” continues to be the menacing background; not only the great majority but also Grundtvig’s cultured contemporaries are included in “ the world” of disbelief. As regards human life and the life of the people (“det menneskelige og folkelige”) the only possibility of escape from world condemnation lies with Christianity; by itself the Danish people belongs to “ the world and what is evil” . Consequently Grundtvig agrees with Spener in attacking the State church which included the faithful as well as those without faith and, thus, abused the ministrations where free acceptance should have been a condition. The State church should be preserved only as a civil frame-system within which the believers might gather to form free congregations. To Grundtvig, also, the true Church embraces the faithful in all religious communities; but the foundation is not the inner religious life common to the pious but “ the historico-Christian Church” everywhere based upon the same baptism and Holy Communion. The kinship between Grundtvig and Spener is typical of the relationship between pietism and 19. century revival theology. Common to both is the emphasis on Christianity as personally acquired “ life” ; the reformatory tension between Law and Gospel is overshadowed by the life and death antithesis. Spener, however, attached little importance to questions of doctrine, whereas Grundtvig’s reaction against rationalism made him emphasize strongly “ the true Christianity” as something definite, historically given through the Church and its sacraments, and, concurrently, as a Gospel outside human control. These two tendencies in Grundtvig’s theology were not always in harmony; in addition there was a lasting conflict between his positive evaluation of natural human life and the dark view of the world which combined with his idea of Christianity. By way of postscript the author comments on an article by Kaj Thaning (Grundtvig Studier, 1966) which was directed against his treatise in Kirkehistoriske Samlinger} 1965.